A indústria do petróleo - disputa por territórios cada vez mais profundos - Dalla Costa, Luiz Alencar (2016)
Energy is today a main strategic factor in human life, which within this moment of economic crisis turns even more central. From the energy sources used today – which is debated due its generation of social, environmental or economic problems – but, which is always defended by those who are willing to retake its rate of capital accumulation – which for petrol is one of the main source for it. Petrol is today, without doubt, one of the most important source of energy in the world which is highly disputed. The recent world invasions and massacres against the people sponsored manly by United States of America targets the control over the petrol sources, especially those in the Middle East. In Brazil the exploitation of this mineral starts with a big struggle “The oil is ours”, with the creation of an important company, Petrobras and of state monopoly. During the nineties, period of neoliberalism, this legal configuration has changed and opened for the open exploitation of private companies. This meant that the companies that exploited the oil were owners of the reserves. With the change to a “neo-developmental” government in 2002 and the discovery of Petrobras of new petrol reserves, called “pre-salt” in 2006, generated the debate on the destination of this important wealth, creating conditions for the approval of a new legal framework for the exploitation of the pre-salt. From 2006 we can see a big move in the industry, especially in Petrobras, which consolidates in Brazil a good condition for the development of this industry. In this study we investigate, today, this powerful oil industry, the major disputes from the point of view of the class struggle, and indicate areas where there is a tendency to deepen disputes in the coming period, understanding the dynamics of these disputes as a constant struggle.